DETERMINATION OF MAIN OUTPUT PARAMETERS FOR HYDROFICATED CONSTRUCTION AND ROAD-BUILDING MACHINES AT OPERATIONAL STAGE OF THEIR LIFE CYCLE - A. N. Maximenko; E. V. Zarovchatskaya; S. V. Maslovskaya (Наука и техника)
Usage efficiency of mechanical engineering products is determined by level of their operating capability. Expenses connected with provision of operating capability for the whole operational period exceed initial cost of the products by 6-10-fold. Moreover , while being used the expenses have a tendency to increase with reduction of output parameters that ensure product application efficiency for its intended purpose. It is necessary to take into account these changes at manufacturing stages of mechanical engineering products. Maximum efficiency can be obtained at the operational stage of the product life cycle only as a result of complex and interrelated measures during designing, manufacturing and usage of the specific product for its intended purpose with due account of its output parameter dynamics. While using the product an analysis of its output parameter dynamics will make it possible to determine maximum value of the operating capability, operational expenses and best practices for obtaining maximum profit per operating time unit.Taking hydroficated excavators of the 5th grade as an example the paper presents dynamics of main output parameters at the operational stage of their life cycle; reveals the main factor influencing on intensity of hydroficated machine operating capability reduction; substantiates an expediency of taking into account output parameter dynamics while evaluating efficiency of its usage; proposes a methodology for determination of or a pay-off time period for recoupment of expenses pertaining to machine procurement and optimum time period for operational stage, its life cycle that corresponds to obtaining maximum profit.Nowadays constant values of main output parameters (operating capability, self cost of machine-hour) corresponding to the beginning of operation are to be taken into account while determining expediency of machine creation. Practically they significantly change in the process of machine operation this fact must be taken account while creating a machine and using it for its intended operational purpose and ensuring its operating capability. The proposed methodology for maintaining and restoration of operating capability of construction and road-building machines was published previously [3]. The paper proposes a methodology for its implementation on the basis of expenses for machine manufacturing and dynamics of main output parameters at the operational stage of its life cycle.